PENINGKATAN AKSES LAYANAN KESEHATAN MASYARAKAT DESA TATAH LAYAP MELALUI PELAYANAN KESEHATAN GRATIS - Yugo Susanto; Alexxander Alexxander; Aulia Rahim; Ahmad Irawan (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Physical condition and geography provide separate obstacles for the community to get access to health service. STIKES ISFI Banjarmasin plays an active role in presenting that solution. The purpose of this activity is to expand the coverage and access of rural communities to health services, build interprofessional collaboration (IPC), apply learning theory, and provide experience to students in community service practices. The activity is carried out using the method of providing free health services through the integration of nursing care practices, medical care, and pharmaceutical care. The activity was carried out in Tatah Layap Village, Banjar, South Kalimantan. Coordination is carried out between STIKES ISFI Banjarmasin, the Bulan Sabit Merah Indonesia (BSMI), and the Village Head of Tatah Layap. The result of this activity is the implementation of free health service activities on Sunday, November 21, 2021. The event takes place at 08.00-12.00 WITA. The activity was attended by 132 people from 7 (seven) Rukun Tetangga (RT) in the village. It can be concluded that this activity is able to help expand the scope and access of the community to health services, build IPC, provide community service experiences to students by applying the knowledge they get on campus.